2016
DOI: 10.1177/1468017316656090
|View full text |Cite
|
Sign up to set email alerts
|

Supporting parents in late modernity through parent education: A mixed-methods study in Hong Kong

Abstract: While the increasing awareness of risk in late modernity has resulted in the proliferation and complication of parental roles and choices, few attempts have been made to explore how parent education can empower parents to reconstruct parenthood and transform parental lives. Based on the results of a mixed-methods study conducted in Hong Kong, this article discusses the possible outcomes and experiences of a parent education program that aimed to facilitate parents' holistic growth in dealing with the prevailin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…With the increase in selfawareness and self-acceptance, their parental self-perception is reconstructed. The accumulated findings on the possible outcomes of the program To, Iu Kan, Tsoi, & Chan, 2015;To, So, Iu Kan, Tsoi, & Chan, 2018;To et al, 2014) have also demonstrated its usefulness in facilitating a healthy parental self-perception among parents in China who are not migrant workers.…”
Section: An Existential-narrative Approach To Parent Education For MImentioning
confidence: 97%
See 4 more Smart Citations
“…With the increase in selfawareness and self-acceptance, their parental self-perception is reconstructed. The accumulated findings on the possible outcomes of the program To, Iu Kan, Tsoi, & Chan, 2015;To, So, Iu Kan, Tsoi, & Chan, 2018;To et al, 2014) have also demonstrated its usefulness in facilitating a healthy parental self-perception among parents in China who are not migrant workers.…”
Section: An Existential-narrative Approach To Parent Education For MImentioning
confidence: 97%
“…In treating identity formation as a social product (Polkinghorne, 2004), the approach understands parental identity as inextricably constructed from interpersonal interactions, particularly parent-child exchanges, within the sociocultural context of parents and their children (To et al, 2018). In treating identity formation as a social product (Polkinghorne, 2004), the approach understands parental identity as inextricably constructed from interpersonal interactions, particularly parent-child exchanges, within the sociocultural context of parents and their children (To et al, 2018).…”
Section: An Existential-narrative Approach To Parent Education For MImentioning
confidence: 99%
See 3 more Smart Citations